IQGAP1 activates PLC‐δ1 by direct binding and moving along microtubule with DLC‐1 to cell surface. Issue 8 (14th June 2019) - Tanaka, Makoto; Osanai, Tomohiro; Homma, Yoshimi; Hanada, Kenji; Okumura, Ken; Tomita, Hirofumi
Abstract: Phospholipase C (PLC)‐δ1, activated by p122RhoGTPase‐activating protein (GAP)/deleted in liver cancer‐1 (p122RhoGAP/DLC‐1), contributes to the coronary spastic angina (CSA) pathogenesis. The present study aims to further investigate the p122RhoGAP/DLC‐1 protein. We examined molecules assisting this protein and identified a scaffold protein—IQ motif‐containing GTPase‐activating protein 1 (IQGAP1). IQGAP1‐C binds to the steroidogenic acute regulatory‐related lipid transfer (START) domain of p122RhoGAP/DLC‐1, and PLC‐δ1 binds to IQGAP1‐N, forming a complex. In fluorescence microscopy, small dots of PLC‐δ1 created fine linear arrays like microtubules, and IQGAP1 and p122RhoGAP/DLC‐1 were colocated in the cytoplasm with PLC‐δ1. Ionomycin induced the raft recruitment of the PLC‐δ1, IQGAP1, and p122RhoGAP/DLC‐1 complex by translocation to the plasma membrane (PM), indicating the movement of this complex is along microtubules with the motor protein kinesin. Moreover, the IQGAP1 protein was elevated in skin fibroblasts obtained from patients with CSA, and it enhanced the PLC activity and peak intracellular calcium concentration in response to acetylcholine. IQGAP1, a novel stimulating protein, forms a complex with p122RhoGAP/DLC‐1 and PLC‐δ1 that moves along microtubules and enhances the PLC activity.